Utilizing Live worksheet Supported by the Vocational Problem-Based Learning (V-PBL) Model for Vocational Students in Merdeka Curriculum: Need Analysis - Nadya Nurhidayah Nurdin; Budiarti Putri Uleng; Musyrifah Mahfuddin (Jurnal Andi Djemma | Jurnal Pendidikan, 2024)
Abstract. This study aims to determine the problems, needs, and desires of teachers and students in utilizing the PBL live worksheet on the Merdeka Curriculum for Indonesian Vocational Teachers and Students as it needs 21st-century competency. Taken the tenth grade of Vocational High School students in South Sulawesi which implemented the Merdeka Curriculum. The data collection techniques in this study were questionnaire tests. The instruments used were interview guides and analysis sheets. The data were analyzed and described qualitatively. The results showed that the current live worksheet material does not reflect the Merdeka curriculum. Therefore, the teachers and students required an English material that is both easy and appropriate for English language acquisition with V-PBL integration for creating an English material that follows the Merdeka curriculum specifically designed for Indonesian Vocational High School students.